2004
DOI: 10.1897/03-254
|View full text |Cite
|
Sign up to set email alerts
|

Organochlorine contaminants in sea turtles: Correlations between whole blood and fat

Abstract: Monitoring toxic organochlorine (OC) compounds is an important aspect in wildlife studies, especially in protected species such as sea turtles. The goal of this study was to determine whether blood OC concentrations can predict those in adipose tissue of sea turtles. Blood offers many benefits for monitoring OCs. It can be collected nondestructively from live turtles and can be sampled repeatedly for continuous monitoring. Organochlorine concentrations in blood may better represent the exposure levels of targe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
75
2
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 104 publications
(90 citation statements)
references
References 37 publications
11
75
2
2
Order By: Relevance
“…Our results demonstrate that the concentrations of the five most abundant PFCs (PFOS, PFNA, PFDA, PFUnA, and PFTriA) in these turtles do indeed rank as expected to their different trophic levels (Table 1). Our findings also support previous studies that showed PFC concentrations to be significantly higher in Kemp's ridleys than in loggerheads ( p < 0.05) [7] and that persistent organic pollutants are observed in decreasing concentrations beginning with Kemp's ridley, loggerhead, leatherback, and then green turtles [12]. Thus, we confirm that these five PFCs biomagnify up marine food webs, and by comparing PFCs in sea turtle species at different trophic levels, we may have a useful tool for examining biomagnification of environmental contaminants.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our results demonstrate that the concentrations of the five most abundant PFCs (PFOS, PFNA, PFDA, PFUnA, and PFTriA) in these turtles do indeed rank as expected to their different trophic levels (Table 1). Our findings also support previous studies that showed PFC concentrations to be significantly higher in Kemp's ridleys than in loggerheads ( p < 0.05) [7] and that persistent organic pollutants are observed in decreasing concentrations beginning with Kemp's ridley, loggerhead, leatherback, and then green turtles [12]. Thus, we confirm that these five PFCs biomagnify up marine food webs, and by comparing PFCs in sea turtle species at different trophic levels, we may have a useful tool for examining biomagnification of environmental contaminants.…”
Section: Discussionsupporting
confidence: 92%
“…Based on their known prey items and assumed trophic status, we hypothesized that PFC concentrations would be lowest in green turtles, followed by increasingly higher levels in hawksbill, leatherback, loggerhead, and Kemp's ridley turtles. Our hypothesis is further justified by previous studies that have compared concentrations of other biomagnifying persistent organic contaminants, such as polychlorinated biphenyls, in adipose tissue among four sea turtle species [12]. Results of these comparisons coincided with trophic status, revealing that green turtles indeed had the lowest concentrations, followed by leatherbacks, loggerheads, and Kemp's ridleys.…”
Section: Introductionsupporting
confidence: 70%
“…In addition to other sources of contaminants, coastal runoff has the potential to pollute the shallow coastal habitats of the Kemp's ridley, and sea turtles, including the Kemp's ridley, are known to bioaccumulate a variety of toxins including organochlorine compounds and heavy metals (Lake et al 1994;Rybitski et al 1995;Pugh and Becker 2001;Kenyon et al 2001;Wang et al 2003;Keller et al 2004Keller et al , 2005Gardner et al 2006). Although their explicit effects on sea turtles have yet to be determined, such exposure may lead to immunosuppression or other hormonal imbalances (J. Keller, National Institute of Standards and Technology, personal communication to J. Seminoff, NMFS, 2006).…”
Section: Other Natural or Manmade Factors Affecting Its Continued Eximentioning
confidence: 99%
“…Preliminary results indicate negative correlations between contaminant concentrations and several health indicators, suggesting that certain levels of contaminants may be capable of inducing immunosuppression in free-ranging sea turtles (Keller et al 2004(Keller et al , 2004aKeller et al 2005;Day et al 2005). To date, much of this work has focused on samples collected from sea turtles in the southeastern United States.…”
Section: Introductionmentioning
confidence: 99%
“…Another area of growing interest involves the effects of environmental contaminants on the health, survival and reproduction of sea turtle populations (Keller et al 2004(Keller et al , 2004aKeller at al 2005;Lake et al 1994). Toxicologists at the National Institute of Standards and Technology (NIST) in Charleston, SC, have been monitoring and investigating the associations between inorganic and organic contaminant concentrations and clinical health parameters in sea turtles.…”
Section: Introductionmentioning
confidence: 99%